Matija Valjavec kot zapisovalec ljudskih pesmi - Kumer, Zmaga (Traditiones (Ljubljana), 2001)
After a careful analysis of Matija Valjavec's notations of folk songs it has become clear that, in the manner of other researchers who been collecting examples of folk songs and writting them down at the time, Valjavec has also "altered" the texts of certain folk songs. His notations were therefore not among the first phonetically accurated descriptions of folk songs. Later on, Valjavec "translated" song text into the dialect of his home town where he had written down these notations
Keywords: Valjavec, Matija, 1831-1897; ethnology; etnologija; ljudsko slovstvo; oral literature; slovensko ljudsko slovstvo; ljudske pesmi; Ethnopoetics